Identification of amendable risk factors for childhood stunting at individual, household and community levels in Northern Province, Rwanda – a cross-sectional population-based study - Albert Ndagijimana; Kristina Elfving; Aline Umubyeyi; Torbjörn Lind (BMC Public Health)
Abstract Background Childhood stunting, defined as height-for-age below − 2 standard deviations (SD), disproportionately affects the Northern Province of Rwanda. We investigated risk factors contributing to stunting in this region at individual, household, and societal/community levels to inform future interventions. Methods We conducted a population-based, cross-sectional study using a quantitative questionnaire in households with children aged 1–36 months in the Northern Province. Anthropometric measurements of children and mothers were taken to estimate nutritional status. Multivariable logistic regressions were performed to identify independent risk factors of stunting, reporting odds ratios, 95% confidence intervals and p-values. Results Overall, stunting prevalence was 27.1% in children aged 1–36 months. At the individual level, boys exhibited 82% higher risk of stunting compared to girls (aOR: 1.82, 95% CI: 1.19, 2.78). Household-level factors such as maternal height and BMI were inversely associated with the risk of childhood stunting (aOR: 0.94, 95% CI: 0.90, 0.97 and aOR: 0.92, 95% CI: 0.86, 0.99, respectively). Other risk factors included no breastfeeding at the time of interview (aOR: 2.00, 95% CI: 1.23, 3.25), presence of twins or triplets aged 1–36 months (aOR: 2.60, 95% CI: 1.21, 5.57), female-headed (single parent) households (aOR: 2.07, 95% CI: 1.00, 4.26), and absence of handwashing facilities near the toilet (aOR: 3.30, 95% CI: 1.36, 7.98). No societal/community factors were significantly associated with childhood stunting in the Northern Province. Conclusion Childhood stunting in the Northern Province of Rwanda is associated with several factors that could lend themselves to interventions, e.g., improved handwashing facilities, improved childcare practices and targeting vulnerable groups such as boys, households with twins or single parents. Additionally, a thorough exploration of identified risk factors through qualitative approaches involving all stakeholders in child and maternal nutrition is warranted.